2019
DOI: 10.2478/s11756-019-00257-4
|View full text |Cite
|
Sign up to set email alerts
|

The anti-invasive activity of Robinia pseudoacacia L. and Amorpha fruticosa L. on breast cancer MDA-MB-231 cell line

Abstract: The paper investigates anticancer effects of methanol extracts of invasive plant species Robinia pseudoacacia L. (RpE) and Amorpha fruticosa L. (AfE) on breast cancer MDA-MB-231 and healthy MRC-5 cells. The anticancer activity was evaluated through examination of cytotoxic effects, anti-invasive potential and impact on redox status in comparative analysis using their chemical composition. According to the IC 50 values, the investigated plants had no significant cytotoxic effects either on healthy cell line MRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…That extract did not express the cytotoxic effect against the palatal mesenchymal stem cells. Cvetković et al [ 41 ] analyzed the cytotoxic activity of methanolic extract of black locust flower obtained using Soxhlet extraction. They concluded that the extract had no significant cytotoxic activity on MRC-5 and MDA-MB-231 (human breast cancer) cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…That extract did not express the cytotoxic effect against the palatal mesenchymal stem cells. Cvetković et al [ 41 ] analyzed the cytotoxic activity of methanolic extract of black locust flower obtained using Soxhlet extraction. They concluded that the extract had no significant cytotoxic activity on MRC-5 and MDA-MB-231 (human breast cancer) cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that all traits were influenced by accessions, a key that may also demonstrate genetic content that probably influences variation. Furthermore, studies have been conducted on the expression of genes associated with drought [25], phenolic constituents [26], proteomic analysis of symbiotic proteins [27], and cancer research [28,29]. The aforementioned research signifies from one point of view the significance of A. fruticosa, although we cannot eliminate the negative effects that it has on ecosystems due to its rapid expansion.…”
Section: Discussionmentioning
confidence: 99%
“…In modern medicine, application have been diversified mainly due to beneficial properties of rotenoids and isoflavones. Therefore, A. fruticosa is used for stimulating immunity, treating diabetes, metabolic disease, and cancer (Cvetković et al, 2019 ; Kozuharova et al, 2017 ; Lee et al, 2006 ; Lee et al, 2016 ), as well as possessing antimicrobial properties and for treating stomach pain, intestinal worms, eczema, neuralgia, carbuncle, burns, wounds, and rheumatism. In search for possible antitumor agents, Li et al ( 1993 ) extracted 8 novel cytotoxic compounds, belonging to rotenoids and isoflavones.…”
Section: Future Prospects In Management Of a Fruticosamentioning
confidence: 99%